PENGARUH PEMBERIAN AIR REBUSAN DAUN UBI JALAR (Ipomea batatas) TERHADAP PENINGKATAN JUMLAH TROMBOSIT PADA IBU HAMIL PENDERITA MALARIA - Sonata Elina Togatorop (Journal of Innovation Research and Knowledge, 2022)
The leaves of sweet potato contains a very high nutritional value, so it can be used as a vegetable and as a herbal remedy. Sweet potato leaves are often found in various regions in Indonesia. This vegetable contains polyphenols that act as antioxidants that fight disease into the body. In the leaves of sweet potato 100g contains 117 mg of calcium, 1.8 mg iron, 3.5 mg carotene, 7.2 mg vitamin C, 1.6 mg vitamin E and 0.5 mg of vitamin K, B vitamins, beta-carotene, as well as protein. Formulation of the problem of this study was to determine whether there are effects of sweet potato leaves boiled water to increase platelet counts in mice. The purpose of this study was to determine the number of platelets which water is boiled sweet potato leaves and boiled water without being sweet potato leaves in. The number of samples from this study there were pregnant woman. From the results of the levels of the number of platelets in the blood samples of mice known to the average levels of platelet counts after being given water boiled sweet potato leaves as much as 210.5 / mm3 of blood and platelet count levels of pregnant woman that were not given water boiled sweet potato leaves as much as 129.7 / mm3 of blood. Statistical analyzes to test differences in the levels of T showed a platelet count between which water is boiled sweet potato leaves and boiled water without being sweet potato leaves, with a value significantly less than 0.05 (5%).